Utilization of Digital Parking Web for the Convenience of Vehicle Users - Wiwoho Mudjanarko, Sri; Zakki Falani, Achmad (ASTONJADRO, 2023)
Humans in their activities need comfort. The comfort that is owned will allow humans to reduce anxiety in unexpected situations. This also applies to the need for parking facilities that are easily accessible from any place and time. Limited access will slow down our planned activities. This problem needs to be solved. This solution can be solved with the use of Web-based IT. The methodology used is to create an application that is easy and convenient for transportation users to find a parking space. The use of the Digital Parking Web is expected to be able to answer the convenience needs of vehicle users while influencing the needs of modern society for transportation. This research is expected to produce an effective parking management web application to support smart cities and their users.